Role of α1-blockers in the current management of hypertension - Li, Hua; Xu, Ting Yan; Chia, Yook Chin *; Buranakitjaroen, Peera; Cheng, Hao Min; Huynh, Minh Van; Sogunuru, Guru Prasad; Tay, Jam Chin; Wang, Tzung-Dau; Kario, Kazuomi; Wang, Ji-Guang (Wiley, 2022)
There is emerging evidence that α1-blockers can be safely used in the treatment of hypertension. These drugs can be used in almost all hypertensive patients for blood pressure control. However, there are several special indications. Benign prostatic hyperplasia is a compelling indication of α1-blockers, because of the dual treatment effect on both high blood pressure and lower urinary tract symptoms. Many patients with resistant hypertension would require α1-blockers as add-on therapy. Primary aldosteronism screen is a rapidly increasing clinical demand in the management of hypertension, where α1-blockers are useful for blood pressure control in the preparation for the measurement of plasma aldosterone and renin. Nonetheless, α1-blockers have to be used under several considerations. Among the currently available agents, only long-acting α1-blockers, such as doxazosin gastrointestinal therapeutic system 4-8 mg daily and terazosin 2-4 mg daily, should be chosen. Orthostatic hypotension is a concern with the use of α1-blockers especially in the elderly, and requires careful initial bedtime dosing and avoiding overdosing. Fluid retention is potentially also a concern, which may be overcome by combining an α1-blocker with a diuretic.